The Role of People's Business Credit (Kur Syariah) on he Turnover of Micro, Small and Medium Enterprises (MSMEs) Customers of PT Pegadaian Syariah in Sampang Regency - Erikawati, Erikawati; Elfira Maya Adiba (Universitas Muhammadiyah Sidoarjo, 2024)
KUR sharia is one of the products offered by Pegadaian Syariah to help micro, small and medium enterprises (MSMEs) develop their businesses using sharia principles. The aim of the research is to analyze the differences in MSME turnover in Sampang Regency before and after receiving sharia KUR financing. This research was carried out from December 2023 to January 2024. The number of samples used was 59 respondents. This research uses comparative quantitative research methods. The data collection and analysis method is through primary data in the form of distributing questionnaires. The data analysis technique used in this research is purposive sampling. The research results show that KUR Syariah financing has a significant influence on the turnover of Micro, Small and Medium Enterprises (MSMEs) in Kab. Lacquer. This is reinforced by the results of data analysis using the paired sample t-test and simple linear regression test, namely the significant value is 0.000 < 0.05 so it can be concluded that after obtaining KUR Syariah financing there has been a significant increase.